Who Owns Culture? : Appropriation and Authenticity in American Law - Scafidi, Susan (Book collections on Project MUSE., 2005)
It is not uncommon for white suburban youths to perform rap music, for New York fashion designers to ransack the world's closets for inspiration, or for Euro-American authors to adopt the voice of a geisha or shaman. But who really owns these art forms? Is it the community in which they were originally generated, or the culture that has absorbed them?While claims of authenticity or quality may prompt some consumers to seek cultural products at their source, the communities of origin are generally unable to exclude copyists through legal action. Like other works of unincorporated group.